Bis[μ-1,2-bis(1,2,4-triazol-4-yl)ethane]bis[diiodidozinc(II)] - Feng, Yunfei (International Union of Crystallography, 2010)
In the title dinuclear complex, [Zn(2)I(4)(C(6)H(8)N(6))(2)], two Zn(II )atoms are bridged by two 1,2-bis(1,2,4-triazol-4-yl)ethane (btre) ligands, forming a centrosymmetric metallacycle. The coordination geometry of the Zn(II) ion is distorted tetrahedral with the coordination sphere formed by two N atoms from the triazole rings of two symmetry-related btre ligands and two iodide ligands.